2004
DOI: 10.1007/s00125-004-1387-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in prevalence of diabetes and impaired glucose tolerance associated with lifestyle transition occurring in the rural population in India

Abstract: Aims/hypothesis. The rural Indian population is undergoing lifestyle transition due to socio-economic growth. This study was done to determine the temporal changes in prevalence of diabetes and IGT that could have occurred in a rural population in India as a result of the lifestyle transition. Methods. A cross-sectional study of 1213 AsianIndian subjects aged 20 years or over was done to look for the prevalence of diabetes and IGT using the 1999 WHO criteria. The temporal changes were assessed in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(57 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…The questionnaire included details on sociodemographic variables, past/family history of hypertension, and physical activity status [6]. Socioeconomic status was assessed using modified Uday-Parikh scale.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire included details on sociodemographic variables, past/family history of hypertension, and physical activity status [6]. Socioeconomic status was assessed using modified Uday-Parikh scale.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Increased prevalence in India is attributed to the life-style transition coupled with urbanization, industrialization and life-style changes. [3]…”
Section: Introductionmentioning
confidence: 99%
“…A review of studies in rural India conducted by Misra and colleagues (2011) found that prevalence increased from 1.9% in 1994 to upwards of 12% in 2009. In addition, rural prevalence rates of impaired glucose tolerance (IGT, a form of pre-diabetes) range from 5.5% to 7.2% (Ramachandran et al 2004). Such figures are concerning, especially considering 72.2% of the Indian population live in rural areas characterized by poverty, isolation, and poor access to health services (Government of India 2011).…”
mentioning
confidence: 99%